Creative arts outreach initiatives in schools: effects on university expectations and discussions about university with important socialisers. Issue 2 (23rd February 2019) - Geagea, Antoinette; Vernon, Lynette; MacCallum, Judith
ABSTRACT: For youth in disadvantaged schools, university expectations and participation are often limited by access to social and cultural capital that support expectations. This study investigated the utility of creative arts outreach initiatives (CAI) in supporting students' university expectations and building cultural capital in homes, schools and neighbourhoods in the southwest corridor of Perth, Western Australia. Cultural capital was operationalised as discussions about university with parents, teachers and friends as important socialisers. The CAI provided task-based programs that connected students with industry professionals and university academics to access new social and cultural capital, develop skills that satisfied learning objectives and increase navigational capacity for higher education participation. Multi-group latent growth models were estimated for university expectations across 3 time points and university discussions with important socialisers at time 3 using a propensity-score matched sample comprising 176 students aged between 11 to 18 years from eight high schools (program group = 88, control group = 88, females = 64%). Results indicated stability in levels of university expectations for program participants and increased discussions about university with parents, teachers and friends. Findings support the inclusion of people-rich, co-curricular creative arts programs such as CAI in disadvantaged schools to build social and cultural capital that supports and potentially widens higher education participation in this region.